Lafoeina longitheca Jaderholm 1904 - M. P. Oliveira 1, 16; S P. Miranda 2, *,; Es W. Mianzan 10,; Ro E. Migotto 11,; Ne B. Nascimento 2, 11; Eli Nogueira Júnior 12,; Er Quiñones 13,; Izio Scarabino 14,; Tín Schiariti 10,; Io N. Stampar 15,; Tronolone 2; , Quíria B.; et al. (Zenodo, 2016)
Lafoeina longitheca Jäderholm, 1904a Distribution in South America: polyp—Pacific Ocean, Chile, from 48°S to 49°S, and at 53.78°S 70.97°W (Galea 2007 p. 38; Galea et al. 2009a p. 328; Galea et al. 2012a p. 24); Atlantic Ocean, at South Georgia Island (Jäderholm 1905; Blanco 1994a). Habitat: polyp—from 10 to 74m depth, on Bougainvillia muscus (Blanco 1994a; Galea 2007 p. 38; Galea et al. 2009a p. 328). : Published as part of M. P. Oliveira 1,16, S P. Miranda 2, *,, Es W. Mianzan 10,, Ro E. Migotto 11,, Ne B. Nascimento 2,11, Eli Nogueira Júnior 12,, Er Quiñones 13,, Izio Scarabino 14,, Tín Schiariti 10,, Io N. Stampar 15,, Tronolone 2, , Quíria B. & Onio C. Marques 2,11, 2016, Census of Cnidaria (Medusozoa) and Ctenophora from South American marine waters, pp. 1-256 in Zootaxa 4194 (1) on page 143, DOI: 10.11646/zootaxa.4194.1.1